First timing constraints on the Ecuadorian Coastal Cordillera exhumation: Geodynamic implications. (January 2021) - Brichau, S.; Reyes, P.; Gautheron, C.; Hernández, M.J.; Michaud, F.; Leisen, M.; Vacherat, A.; Saillard, M.; Proust, J.N.; O'Sullivan, P.
Abstract: In this study, we provide the first detrital apatite (U–Th-Sm)/He (AHe) and zircon U–Pb ages to establish a detailed short-term chronology of the burial and exhumation history, which occurred in the Coastal Cordillera along the forearc domain of Ecuador. First, our results allowed us to define a range of maximum deposition ages for the Angostura Formation from 9.6 ± 0.2 Ma to 11.5 ± 0.6 Ma, which records high enough temperatures to partially reset AHe ages. QTQt thermal inverse modeling of the AHe dataset reveals three main periods of exhumation along the Costal Cordillera at ∼2 Ma, ∼5–6 Ma and ∼8–10 Ma, independent of the sample geographic locations. We discuss the origin of these periods of exhumation in relation to the geodynamic frame. The oldest exhumation event, at ∼8–10 Ma, evidenced locally along fault systems, could be related to overriding plate kinematic changes or early arrival of Carnegie Ridge. The intermediate exhumation period, at ∼5–6 Ma, could be explained by a later arrival of the Carnegie Ridge or to the subduction of an along-strike positive relief of the ridge. Later, subduction of sea-floor asperities could be responsible for heterogeneous uplift of the Coastal Cordillera during the Pleistocene (∼2 Ma) that induced exhumation as supported by our models. These results are corroborated by previous studies and demonstrate that AHe data are sensitive enough to provide reliable constraints in sedimentary domains. Highlights: Three main periods of exhumation have been recognized in the Coastal Cordillera of Ecuador. Overriding plate kinematic changes can play a significant role in exhumation processes. The Apatite (U–Th-Sm)/He thermochronometer is sensitive enough to provide reliable constraints in sedimentary domains.